Circulating epigenetic biomarkers for detection of recurrent colorectal cancer. Issue 7 (7th January 2020) - Symonds, Erin L.; Pedersen, Susanne K.; Murray, David; Byrne, Susan E.; Roy, Amitesh; Karapetis, Christos; Hollington, Paul; Rabbitt, Philippa; Jones, Frederick S.; LaPointe, Lawrence; Segelov, Eva; Young, Graeme P.
Abstract : Background: The sensitive detection of recurrent colorectal cancer (CRC) by the measurement of circulating tumor DNA (ctDNA) might improve the chance of a cure. This study compared a quantitative methylated ctDNA test with carcinoembryonic antigen (CEA) in the setting of surveillance for recurrence. Methods: Blood samples collected either during surveillance or within 12 months of the confirmation of recurrence were assayed for ctDNA (methylated branched‐chain amino acid transaminase 1 [ BCAT1 ]/Ikaros family zinc‐finger 1 protein [ IKZF1 ]) and CEA. The optimal ctDNA threshold was determined by receiver operating characteristic analysis, and the test performance for the detection of recurrence was compared with CEA (5 ng/mL threshold). Results: The study cohort comprised 144 eligible patients and included 50 recurrence events. The sensitivity of the methylated ctDNA test for recurrence was 66.0% (95% confidence interval [CI], 57.1%‐69.3%), which was significantly higher than the sensitivity of CEA (31.9%; 95% CI, 22.8%‐36.6%; P < .001). The sensitivity for resectable recurrence (n = 20) was also higher (ctDNA, 60.0%; CEA, 20.0%; P = .01). The specificity did not differ between the tests (ctDNA, 97.9%; 95% CI, 93.2%‐99.6%; CEA, 96.4%; 95% CI, 91.4%‐99.0%). When adjustments were made for other predictors of the presence of recurrence, a positive ctDNA test was an independent predictor (odds ratio, 155.7; 95% CI, 17.9‐1360.6; P < .001), whereas CEA was not (odds ratio, 2.5; 95% CI, 0.3‐20.6; P = .407). Conclusions: The quantitative ctDNA test showed superior sensitivity in comparison with CEA without a difference in the specificity for detecting recurrent CRC. Longitudinal studies are warranted to further assess the utility (specifically the survival benefit) of methylated BCAT1 / IKZF1 ctDNA in the surveillance of patients with CRC. Abstract : An optimal positivity threshold has been determined for an epigenetic circulating tumor DNA panel of biomarkers (methylated BCAT1 and IKZF1 ), and it has been applied to investigating the panel's utility in the detection of colorectal cancer recurrence. The sensitivity of the circulating tumor DNA test is superior to that of the clinically used carcinoembryonic antigen test for all recurrences (66% vs 32%) and those considered curable (60% vs 20%), with both tests having a very high specificity (98% vs 96%).